STUDYING ON TEACHING FLUTE FOR FIRST YEAR STUDENT MUSIC EDUCATION MAJOR IN HAINAN UNIVERSITY, HAINAN PROVINCE, THE PEOPLE’S REPUBLIC OF CHINA - Jiahou, Yin; Banchongsilpa, Orawan (Asia Pacific Journal of Religions and Cultures, 2025)
The purpose of this study is to study the teaching method of flute for the first-year students in Hainan University. The research method is qualitative research, and the samples are first-year students in Hainan University. The research tools are: interview form, observation form and verification form. The results show that: (1) Flute teaching is a comprehensive training process aimed at improving students' playing skills, musical expression and learning interest, including the systematic training of basic skills (such as breath control, timbral shaping, fingering training) and advanced skills (such as rapid breathing, continuous playing). (2) Flute teaching method is an important part of music education, aiming at cultivating students' musical perception ability and sense of rhythm. In order to comprehensively evaluate and optimize the teaching effect of flute teaching method, from the Professional quality of teachers, Teaching process, Student participation, teaching tools, Teaching objectives, Teaching content and Teaching methods seven aspects of flute teaching methods were observed and formed. (3) The IOC result of the interview form was 0.93 higher than 0.75. It is permitted for research purposes. (4) The IOC result of the observation table is 0.95 higher than 0.6. It is permitted for research purposes.